PENGARUH PRODUCT PLACEMENT DALAM DRAMA KOREA VINCENZO TERHADAP BRAND IMAGE KOPIKO - Praminia, I Gusti Agung Ayu Rahma; Purnawan, Ni Luh Ramaswati; Gelgel, Ni Made Ras Amanda (E-Jurnal Medium, 2022)
To increase the effectiveness of advertising by using television media, marketers use advertising strategies that can provide information about the brand without disturbing the audience when watching the desired program.The advertising strategy currently used by marketers is called Product Placement. Th e purpose of this study is to explains the Influence of Product Placement in the Korean Drama Vincenzo on Brand Image Kopiko. This research is explanatory research , data was collected with the survey by distributing questionnaires to 459 respondents with predetermined criteria, to analyze the findings of data on the effect of variable product placement on brand image, the researcher used a simple linear regression statistical test. From these results, it shows that the effect of product placement in the Korean Drama Vincenzo on Kopiko’s brand image is 27%. There is a significant influence between the product placement variable in the Korean Drama Vincenzo and the Kopiko brand image.  Keywords : Product Placement, Vincenzo Korean Drama, Brand Image, Kopiko